2010
DOI: 10.1128/jvi.01941-09
|View full text |Cite
|
Sign up to set email alerts
|

The Prostate Cancer-Associated Human Retrovirus XMRV Lacks Direct Transforming Activity but Can Induce Low Rates of Transformation in Cultured Cells

Abstract: The human retrovirus XMRV (xenotropic murine leukemia virus-related virus) is associated with prostate cancer, but a causal relationship has not been established. Here, we have used cultured fibroblast and epithelial cell lines to test the hypothesis that XMRV might have direct transforming activity but found only rare transformation events, suggestive of indirect transformation, even when the target cells expressed the human Xpr1 cell entry receptor for XMRV. Characterization of cells from three transformed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…In this regard, APOBEC3G is absent in prostate cancer lines, suggesting that such cells provide an optimal environment for XMRV infections (2,27). The early targeting of prostate epithelium by XMRV suggests that the virus finds it a preferential site, and even though our studies showed lack of continued replication in vivo, chronic persistent infection could play a role in disrupting homeostasis and promoting cell cycle dysfunction (22). Since the completion of this study, an additional four reports suggested that XMRV detection in specimens collected from human patients might be the result of laboratory contamination (12,25,30,33), further fueling the controversy as to whether XMRV is a human retrovirus and questioning its causative link to pathogenesis.…”
Section: Discussionmentioning
confidence: 76%
“…In this regard, APOBEC3G is absent in prostate cancer lines, suggesting that such cells provide an optimal environment for XMRV infections (2,27). The early targeting of prostate epithelium by XMRV suggests that the virus finds it a preferential site, and even though our studies showed lack of continued replication in vivo, chronic persistent infection could play a role in disrupting homeostasis and promoting cell cycle dysfunction (22). Since the completion of this study, an additional four reports suggested that XMRV detection in specimens collected from human patients might be the result of laboratory contamination (12,25,30,33), further fueling the controversy as to whether XMRV is a human retrovirus and questioning its causative link to pathogenesis.…”
Section: Discussionmentioning
confidence: 76%
“…NZB virus infection showed intermediate toxicity, with cell death being apparent in 11 to 12 days. Note that we previously reported that XMRV infection was not toxic to mink cells (22), but the virus used for infection in that study was a mixture of XMRV and the LAPSN vector. The LAPSN vector replicates more efficiently than XMRV in coinfected cells (22), and this may explain why the virus mixture showed no toxic effects.…”
Section: Xmrv Induces Apoptosis In Sy5y Neuroblastoma Cellsmentioning
confidence: 99%
“…We first tested XMRV for a possible transforming activity that might explain a role for XMRV in prostate cancer but found no evidence that XMRV was acutely oncogenic (22). We next explored the possibility that XMRV was neurotoxic and that this might explain a role for XMRV in the neuromuscular disease aspects of CFS.…”
mentioning
confidence: 99%
“…Furthermore, XMRV was found at high titers in the 22Rv1 human prostate cancer cell line (20) and was recently shown to have most likely originated from recombination between two different endogenous murine retrovirus sequences during derivation of the 22Rv1 human prostate cancer cell line by serial passage of a human prostate tumor xenograft in nude mice (21,22). These findings have led to the general scientific consensus that XMRV is not a human retrovirus but a novel recombinant murine retrovirus with some unique biological properties (23). XMRV has a broad host range and can infect a variety of human cell lines in vitro (24)(25)(26)(27) and nonhuman primate cells and tissues in vivo (5,28).…”
mentioning
confidence: 97%